Antibacterial Shoe Insole-Coated CuO-ZnO Nanocomposite Synthesized by the Sol-Gel Technique. (17th December 2020) - Vo, Nguyen Lam Uyen; Van Nguyen, Thi Thuy; Nguyen, Tri; Nguyen, Phung Anh; Nguyen, Van Minh; Nguyen, Ngoc Huy; Tran, Van Linh; Phan, Ngoc Anh; Huynh, Ky Phuong Ha
Abstract : In this study, CuO-ZnO composite was synthesized via the sol-gel method using oxalic acid to form the medium complex and its applications in antibacterial have been conducted with B. cereus, E. coli, S. aureus, Salmonella, and P. aeruginosa . Then, nanopowder of CuO-ZnO was coated on shoe insoles and their antibacterial effect with S. aureus was tested. The nanocomposite products were characterized by XRD, XPS, SEM, TEM, and UV-Vis. The results showed that the CuO-ZnO composite has the average particle size in a range of 20-50 nm, the point of zero charge of 7.8, and the bandgap of 1.7 eV. XPS result shows the composite structure with Cu 2+ in the product. The minimum inhibitory concentration (MIC) of CuO-ZnO nanocomposite was 0.313 mg·mL -1 for S. aureus and Samonella, 0.625 mg·mL -1 for E. coli, and 5 mg·mL -1 for B. cereus and P. aeruginosa . The shoe insoles coated with 0.35 wt.% of CuO-ZnO nanocomposite also had high antibacterial activity against S. aureus, and this antibacterial nanocomposite was implanted durably on the surface of the shoe insoles.